Gold Coast Food - Field, Margaret (Petits Propos Culinaires, 1993)
One of the grottiest photocopies we have ever received, or indeed seen, was sent to us by Professor Robert J. Theodoratus of Colorado State University in 1987. He wrote:  Here is a photocopy of my photocopy of that now very rare pamphlet on food in what is today Ghana, especially the southern area: 'Gold Coast Food' by Margaret J. Field; Achimoto, at the College Press, 1931. It was very difficult for me to locate a copy. In fact it took me almost 2 1/2 years searching via my university's interlibrary loan service. Eventually they did get a photocopy from the University of Ghana at Achimoto. They were unable to locate a copy in any library in the UK. I once wrote Sir Raymond Firth who is now retired from the Department of Social Anthropology at the London School of Economics trying to locate a copy. He said that he once did have a copy given him by Dr Field who was in part one of his early students in London. When Professor Firth retired he gave this item to his University Library along with many other items but his search found it missing from that library! He was not overly happy about this. Margaret Field was trained both in social anthropology and clinical psychology and is best remembered today for some of the finest ever books and articles on problems of mental health in West Africa and for her monographs in social anthropology for the same area. Take a careful look at this item. I would encourage you to perhaps reprint it as an article in PPC. It does contain some very important information for its time on food and cooking in what is now Southern Ghana.  Professor Gerald Mars kindly contacted Sir Raymond Firth on our behalf, to confirm that so far as Sir Raymond was concerned our reprinting Margaret Field's essay would be welcome, both generally and because it would permit the replacing of the lost copy in the library of London University (besides depositing copies in other appropriate libraries, which we shall not fail to do). If any readers of PPC are able to put us in touch with surviving relations of Margaret Field, we should be very pleased; they too would no doubt like copies of her essay. In reprinting the essay we have made no changes except for the replacement of a few phonetic symbols which were in use in the 1930s for transcribing African names but which are no longer current, and for replacing 'cocoa-nut' by 'coconut' and 'cocoa-yam' by coco-yam. Gerald Mars himself adds the following introductory comments on the article, which begins on the next page.  In 1931, when Dr Margaret Field's pioneering pamphlet on Gold Coast Food was published, it was not destined to make much impact; an interest in the recipes and diets of indigenous peoples was not to emerge for several decades. She was thus well ahead of her time - even Audrey Richards' acclaimed study of diet in Rhodesia did not appear for a further eight years. Margaret Field was a woman of rare qualifications: she was also something of a mystery. As an anthropologist she was already the member of a very small band indeed, while women anthropologists could, at that time, be counted on one hand. But besides earning a doctorate in anthropology, Margaret Field was also a qualified medical doctor, a psychiatrist and, for completeness, the holder of an honours degree in chemistry. These various talents combine to make 'Gold Coast Food' both interesting and valuable. This pamphlet's appearance in PPC represents, as the editors have explained, the end of a treasure trail, and another element of mystery. What happened to the one copy known to exist in the UK? Was the copy finally located in Ghana by Professor Theodoratus the last surviving copy in the world? What took Margaret Field to the Gold Coast is also something of a mystery; it was still known as 'The White Man's Grave' and fieldwork must have been extremely hazardous. We know nothing of her family. We do know that she went on to produce several anthropological monographs on different peoples of the Gold Coast; that she worked through indigenous languages and that she appears to have finally retired to Dulverton in Somerset where she published fiction under the pen name Mark Freshfield. A remarkable woman.  The situation of the 'Gold Coast' (now Ghana) is shown in this sketch map. A serious Gold Coast cookery book published more than two decades after Margaret Field's essay is Gold Coast Nutrition and Cookery, the Gold Coast Government and Thomas Nelson, 1953; hard to find but very useful and, like the present essay, rich in local names for dishes and ingredients.